×+y=3.
2×+y=6
com a metadomais comvisete
Soluções para a tarefa
Respondido por
2
O método da adição
x+y=3 (×-1)
2x+y=6
-x -y =-3
2x +y=6
______
x = 3
Substituir em qualquer linha
x+y=3
3+y=3
y=3-3
y=0
S={3,0}
x+y=3 (×-1)
2x+y=6
-x -y =-3
2x +y=6
______
x = 3
Substituir em qualquer linha
x+y=3
3+y=3
y=3-3
y=0
S={3,0}
Perguntas interessantes
Geografia,
9 meses atrás
Artes,
9 meses atrás
Matemática,
9 meses atrás
Matemática,
1 ano atrás
Inglês,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás